GLOBAL MEDIA FRAMING OF JUNGKOOK’S 2022 FIFA WORLD CUP PERFORMANCE: CULTURAL DIPLOMACY AND NATION BRANDING - Firdausi, Farikha 'Ulya; Jatmika, Sidik (Universitas Padjadjaran, 2025)
This study examines how international media framed Jungkook’s performance at the opening ceremony of the 2022 FIFA World Cup within the broader context of South Korea’s cultural diplomacy and soft power. In this study, cultural diplomacy is understood as the strategic use of popular culture and global cultural figures to promote national image and influence international perceptions. Using a qualitative descriptive approach, this research employs content analysis supported by NVivo 15 to analyze 52 online news articles drawn from five regional clusters: South Korea, ASEAN, the Middle East, South Asia, and Western countries. The analysis is guided by Entman’s framing theory (1993), focusing on four key dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Each article was thematically coded to identify both manifest and latent meanings related to cultural diplomacy and nation branding, while sentiment analysis was used to assess the tone of media coverage. The findings indicate that positive framing predominates across all regions, frequently portraying Jungkook as a global cultural representative and symbol of South Korea’s soft power. Most media coverage emphasizes his role in promoting Korean culture and enhancing the country’s international image. A smaller proportion of coverage, particularly in ASEAN and Western media, raises critical perspectives related to cultural dominance and commercialization. These findings suggest that global media narratives contribute to the construction of national image and the projection of cultural influence through popular culture in international mega-events. The study highlights the intersection between media representation, entertainment, and diplomacy in shaping contemporary global cultural discourse.